Modulatory actions of o-coumaric acid on carcinogen-activating cytochrome P450 isozymes and the potential for drug interactions in human hepatocarcinoma cells*. (September 2015) - Sen, Alaattin; Terzioglu, Gulsum; Atmaca, Pelin; Celik, Gurbet; Ozgun, Ozden; Arslan, Sevki
Abstract Context: Although humans are exposed to o-coumaric acid (OCA) in their diet, there is no available literature related to drug interaction and the carcinogen-activating potential of OCA in the HepG2 cell line. Objective: This study was undertaken to determine the effects of OCA on the cytochrome P450 (CYP) 1A2, CYP2E1, CYP2C9, and CYP3A4 enzymes, which are primarily involved in carcinogen and drug metabolism. Materials and methods: The cytotoxicity of OCA in HepG2 cells was investigated by measuring the cleavage of WST-1. The protein and mRNA levels of CYPs were determined by western blotting and RT-PCR, respectively. Results: The EC10, EC25, and EC50 values of OCA were calculated to be 1.84, 3.91 and 7.39 mM, respectively. A sublethal dose of 5 mM was used throughout this study. The CYP1A2 protein and mRNA levels were increased by 52 and 40% (p < 0.05), as were the CYP2E1 levels by 225 and 424%, respectively (p < 0.05). However, OCA treatment caused 52 and 60% decreases in the levels of CYP3A4 protein and mRNA (p < 0.05), respectively. In contrast to CYP3A4, the CYP2C9 protein and mRNA levels increased by 110 and 130%, respectively. Discussion and conclusion: Co-administration of OCA with some drugs may lead to undesirable food–drug interactions due to modulatory effects on CYP isozymes involved in drug metabolism. Moreover, exposure to OCA may cause an increase in carcinogenicity and toxicity due to the induction of the CYP isozymes involved in chemical carcinogenesis. Therefore, serious precautions should be taken when using OCA as a supplement.